NEUROPEDAGOGICAL FOUNDATIONS FOR DEVELOPING STUDENTS’ INFORMATION LITERACY AND READING CULTURE (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the neuropedagogical foundations for developing students’ information literacy and reading culture in contemporary education. The relevance of the study is determined by the growing complexity of the information environment, the expansion of digital texts, and the need to prepare learners for conscious, critical, and responsible interaction with different sources of knowledge. Information literacy is interpreted not only as the ability to search for and use information, but also as a cognitive and metacognitive process that includes attention control, source evaluation, verification, comparison, interpretation, and ethical use of information. Reading culture is considered as a stable personal and educational quality that involves motivation for reading, deep comprehension, reflective interpretation, aesthetic perception, and the ability to connect textual meaning with personal and social experience. The article emphasizes that both phenomena are based on the interaction of attention, memory, thinking, emotion, motivation, and metacognitive regulation. From a neuropedagogical perspective, effective development of information literacy and reading culture requires organizing learning in accordance with the natural mechanisms of brain activity, cognitive load, emotional engagement, and active learning. The study highlights the importance of learner-centered tasks, meaningful reading strategies, critical analysis of sources, reflective discussion, and digital reading practices. The results of the analysis show that the integration of information literacy and reading culture creates conditions for the formation of independent, critical, and culturally developed learners who are able to understand, evaluate, and use information responsibly in academic and social contexts.